SLCO1B1 Genetic Variant Associated With Statin‐Induced Myopathy: A Proof‐of‐Concept Study Using the Clinical Practice Research Datalink. Issue 6 (13th August 2013) - Carr, D F; O'Meara, H; Jorgensen, A L; Campbell, J; Hobbs, M; McCann, G; van Staa, T; Pirmohamed, M
<x xml:space="preserve">Abstract</x> This study aimed to determine whether patients with statin‐induced myopathy could be identified using the United Kingdom Clinical Practice Research Datalink, whether DNA could be obtained, and whether previously reported associations of statin myopathy with the SLCO1B1 c.521T>C and COQ2 rs4693075 polymorphisms could be replicated. Seventy‐seven statin‐induced myopathy patients (serum creatine phosphokinase (CPK) > 4× upper limit of normal (ULN)) and 372 statin‐tolerant controls were identified and recruited. Multiple logistic regression analysis showed the SLCO1B1 c.521T>C single‐nucleotide polymorphism to be a significant risk factor (P = 0.009), with an odds ratio (OR) per variant allele of 2.06 (1.32–3.15) for all myopathy and 4.09 (2.06–8.16) for severe myopathy (CPK > 10× ULN, and/or rhabdomyolysis; n = 23). COQ2 rs4693075 was not associated with myopathy. Meta‐analysis showed an association between c.521C>T and simvastatin‐induced myopathy, although power for other statins was limited. Our data replicate the association of SLCO1B1 variants with statin‐induced myopathy. Furthermore, we demonstrate how electronic medical records provide a time‐ and cost‐efficient means of recruiting patients with severe adverse drug reactions for pharmacogenetic studies. Clinical Pharmacology & Therapeutics (2013); 94 6, 695–701. doi:10.1038/clpt.2013.161